1998
DOI: 10.1093/nar/26.22.5017
|View full text |Cite
|
Sign up to set email alerts
|

Universal rules and idiosyncratic features in tRNA identity

Abstract: Correct expression of the genetic code at translation is directly correlated with tRNA identity. This survey describes the molecular signals in tRNAs that trigger specific aminoacylations. For most tRNAs, determinants are located at the two distal extremities: the anticodon loop and the amino acid accepting stem. In a few tRNAs, however, major identity signals are found in the core of the molecule. Identity elements have different strengths, often depend more on k cat effects than on K m effects and exhibit ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
928
3
8

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 754 publications
(955 citation statements)
references
References 240 publications
16
928
3
8
Order By: Relevance
“…In contrast, for tRNAs with identity elements distributed over the whole structure (especially the anticodon position), aminoacylation of the minihelix is generally weak as shown for the IleRS, ValRS, and methionyl-tRNA synthetase (MetRS) systems (20,29,39). A. aeolicus tRNA Leu belongs to the type II tRNA group with an extra variable loop, and its anticodon loop is not necessary for aminoacylation as E. coli tRNA Leu (40,41). However, the aminoacylation level of minihelix Leu is low.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for tRNAs with identity elements distributed over the whole structure (especially the anticodon position), aminoacylation of the minihelix is generally weak as shown for the IleRS, ValRS, and methionyl-tRNA synthetase (MetRS) systems (20,29,39). A. aeolicus tRNA Leu belongs to the type II tRNA group with an extra variable loop, and its anticodon loop is not necessary for aminoacylation as E. coli tRNA Leu (40,41). However, the aminoacylation level of minihelix Leu is low.…”
Section: Discussionmentioning
confidence: 99%
“…eEF1α may preferentially bind m 1 Amethylated tRNA. It is also possible that the methylated tRNAs are preferentially aminoacylated and subsequently recognized by eEF1α, although fully unmodified tRNAs can be readily charged in vitro, and many tRNA synthetases are not known to interact with the tRNA region where m 1 A58 resides (Giegé et al, 1998).…”
Section: A Methylated Trnas Are Enriched In Polysomesmentioning
confidence: 99%
“…The validity of this assumption is by no means guaranteed, however. For instance, in vivo and in vitro tRNA identity conversion experiments (Giegé et al, 1998;Hou and Schimmel, 1988;McClain and Foss, 1988;McClain et al, 1991;Normanly et al, 1992) ascertained that functional equality or differences can be revealed irrespective of sequence similarities. It is known that tRNAs that have quite similar sequences may be charged by different amino acids, whereas some isoacceptor tRNAs are quite dissimilar if compared using sequential information.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that tRNAs that have quite similar sequences may be charged by different amino acids, whereas some isoacceptor tRNAs are quite dissimilar if compared using sequential information. This is because some characteristic structural features (sets of relatively few sequence elements) can be major determinants of the functional identity of tRNAs (Giegé et al, 1998(Giegé et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%